The effects of changes in climate and food supply on the timing of reproduction in Great Skuas (Stercorarius skua) and Arctic Skuas (Stercorarius parasiticus) - Stolk, Shaylon Blair (2011)
This paper will examine the relationship between marine predators and disruptions of the Shetland and North Sea fishery due to anthropogenic climate change. The frrst chapter will give an overview of localized climate patterns in Shetland and the wider ocean areas, with some original analysis of raw climate data from the region. Climate models specific area will be used to determine if statistically significant trends in ocean temperature exist in the southern North Sea outside of the normal cyclic climate patterns known as the North Atlantic Oscillation and the Arctic Oscillation. Winter sea surface temperature will be used throughout as a proxy for climate variation, as this is more stable an indicator than air temperature, and more relevant to the life cycles of pelagic organisms. Confrrming the presence of climate change in the study area is necessary to posit a causal link between climate change and alterations in the region's ecosystem. The Shetland plankton community is the topic of the second chapter, with statistical analysis of relationships between plankton types and climate change, as well as interactions within the plankton community. The frrst focus of the chapter is to determine if a significant relationship exists between variation in climate and the life cycle of phytoplankton, specifically diatoms, which are the most abundant species. The second is to determine the nature of the relationship, if any, between diatom life cycle and productivity and the success of zooplankton-specifically copepods, Chapter Three examines the relationship between sandeels and copepods, which are their preferred food species. Both copepod population and the timing of the population peak are considered as possible drivers of sandeel population success. Furthermore, the possibility of a direct link between sea surface temperature and sandeel numbers is explored using regression analysis. 7 Finally, we examine the relationship between seabird phenology, sandeel biomass by using the Great and Arctic Skuas nesting on ...